The Influence of Taxpayer Awareness, Turnover, and Tax Sanctions on Restaurant Taxpayer Compliance - Galuh Putra Wicaksono (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
The objective of this study is to analyze the effect of taxpayer awareness, turnover, and tax sanctions on restaurant taxpayer compliance in Madiun. The research sample is 170 restaurant taxpayers registered at the Madiun Regional Revenue Agency. The research method used is quantitative method. The data analysis tools used are multiple linear regression tests. The data analysis results show that taxpayer awareness affects restaurant taxpayer compliance in Madiun, while turnover and tax sanctions have no effect on restaurant taxpayer compliance in Madiun. This matter occurs, due to many respondents have less knowledge about taxation so that taxpayers prioritize awareness in the taxpayer's personal in their personal tax. The results of data analysis through the F test show that taxpayer awareness, turnover, and tax sanctions simultaneously affect restaurant taxpayer compliance in Madiun. This shows that taxpayer awareness, turnover, and tax sanctions together are able to influence the level of compliance of restaurant taxpayers in Madiun.